How Is AI Enhancing Investment Behavior in Today's Financial Markets - Yao, Mengxiao (Transactions on Computer Science and Intelligent Systems Research, 2024)
The present investigation delves intricately into AI's pivotal function in shaping contemporary financial market investment dynamics. Amidst surging data volumes and computational leaps, AI has emerged as a cornerstone in finance, particularly in enhancing investment efficacy, risk assessment, and tailored services. By scrutinizing AI's present adoption across domains like data analysis, algorithmic trading, risk mitigation, and advisory services through concrete case studies, we illustrate their tangible impact. Our study subsequently unfolds how AI bolsters investment activities by expediting decision-making, refining strategic investments, reinforcing risk controls, and enriching user experiences. Furthermore, we delve into the technological hurdles, ethical dilemmas, and regulatory challenges encountered in AI's financial sector integration. Lastly, we propose recommendations for financial institutions and regulators to foster AI's sustainable growth within the market. This research not only contributes to a profound comprehension of AI's role in financial applications but also furnishes valuable insights and future research directions.